The trainer's handbook - Lawson, Karen (John Wiley & Sons, 2016)
"A ready-to-use toolkit for delivering high-value training in any scenario The Trainer's Handbook is a comprehensive manual for designing, developing, and delivering effective and engaging training. Based on the feedback of workshop participants, readers, and instructors, this new third edition has been expanded to provide guidance toward new technologies, leadership training, distance learning, blended learning, and other increasingly common issues, with new case studies for each chapter. A systematic approach to training breaks the book into five parts that separately target analysis, design, development, delivery, and evaluation, giving you a comprehensive reference designed for quick look-up and easy navigation. New inventories, worksheets, job aids, checklists, activities, samples, and templates help you bring new ideas into the classroom, and updated instructor guide help you seamlessly integrate new and established methods and techniques. Training is increasingly expanding beyond the traditional instructor-led classroom; courses may now be delivered online or offsite, may be asynchronous and self-led, and may be delivered to individuals, small groups, or entire organizations. This book gives you a one-stop reference and toolkit to help you provide more effective training, regardless of class size, structure, subject, or objective. Explore new training styles adapted to different learning styles Design specialized instructional plans for groups, distance learning, and active training Blend creativity, logic and design principles to create more effective visuals Develop strategies for training leaders, training across cultures, and more Effective training means delivering useful information in a way that's accessible, approachable, understandable, and memorable. The Trainer's Handbook gives you the knowledge and framework you need to provide a high-value experience in any training scenario"--